La relación de Helicobacter pylori con la displasia y el cáncer gástrico en Costa Rica - Miranda, M (1998)
Occurrence of the bacterium Helicobacter pylori was compared for two Costa Rican sites with contrasting levels of gastric cancer incidence, Poás (incidence 15. 13%) and Puriscal (83. 53%). A sample of 1 85 adults of similar age and sex proportions was studied in each site, using both H. pylori antiserum tests and gastroscopy to collect two biopsies per case. No c1ear association between H. pylori and gastric cancer was found.